2009
DOI: 10.1590/s1806-37132009000300012
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography findings of postoperative complications in lung transplantation

Abstract: improved as a result of advances in surgical technique, careful harvesting/preservation of donor organs, improvements in immunosuppressive therapy and earlier recognition of complications with the use of various imaging techniques. The reported one-, five-, ten-and fifteen-year survival rates are 75%, 50%, 35% and 25%, respectively. (3,4) The most common cause of mortality in the first 6 months is bacterial infection, which is thereafter supplanted by chronic graft dysfunction. The clinical and radiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Imaging techniques, particularly HRCT, play an important role in the diagnosis of PIBO (17,18). A number of characteristics are observed on PIBO-positive HRCT scans, including patchy ground-glass opacity, air retention, bronchial wall thickening, bronchiectasis, mosaic perfusion and a unilateral hyperlucent lung (19). Air retention syndrome has the highest sensitivity and accuracy in the diagnosis of BO.…”
Section: Diagnostic -------------------------------------------------mentioning
confidence: 99%
“…Imaging techniques, particularly HRCT, play an important role in the diagnosis of PIBO (17,18). A number of characteristics are observed on PIBO-positive HRCT scans, including patchy ground-glass opacity, air retention, bronchial wall thickening, bronchiectasis, mosaic perfusion and a unilateral hyperlucent lung (19). Air retention syndrome has the highest sensitivity and accuracy in the diagnosis of BO.…”
Section: Diagnostic -------------------------------------------------mentioning
confidence: 99%
“…7 An aspect that is unique to lung transplantation in pediatric recipients is the issue of graft growth. Although a study by Ro et al, 8 using serial CT scans, suggested that tracheal growth in lung transplant recipients may be similar to that in normal children, insufficient growth at the bronchial anastomosis sites remains a potential substrate for the development of stenosis late after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…A chest X-ray may only show features suggestive of advanced stages of rejection (bronchiectasis, pleural effusion) or help detect alternative diagnoses such as cardiac failure [26]. Since the early diagnosis and treatment of infection or rejection is essential, HRCT images are evaluated to make alternative diagnoses and choose the location for biopsy sampling at bronchoscopy, with subsequent sample assessment by a transplant-experienced pathologist [20,26,27,28]. HRCT alone is not sufficiently specific and sensitive to reliably diagnose rejection.…”
Section: Home Spirometry Lung Function Over Time and Signs Of Rejectionmentioning
confidence: 99%
“…In acute rejection, HRCT findings may include ground-glass opacities (often with basal distribution), peribronchial cuffing, septal thickening and new or more extensive pleural effusion. In chronic rejection, dilated bronchi, bronchiectasis, mosaic attenuation and air trapping (on expiratory scans, more pronounced in the lower lobes) may be observed [27,29]. Bronchoscopic biopsies may contribute to the tissue diagnosis of acute rejection [29,30].…”
Section: Home Spirometry Lung Function Over Time and Signs Of Rejectionmentioning
confidence: 99%
See 1 more Smart Citation